Perbedaan Massage Payudara dengan Teknik “Z” Dan “Buku Jari Tangan” Terhadap Produksi ASI - Ana Rofika; Uswatun Kasanah (PROFESSIONAL HEALTH JOURNAL, 2024)
Introduction: The decrease in breast milk production in the first days after giving birth can be caused by a lack of stimulation of the hormones oxytocin and prolactin which play a very important role in the smooth flow of breast milk, causing breast milk not to come out immediately after giving birth, the baby having difficulty sucking because the mother's nipples are not supported. Currently, in midwifery services, complementary-based services have emerged which are often performed, including breast massage to overcome irregularities in breast milk production. Breast massage is breast massage, which is gentle massaging of the breasts which can be done every day. This study aims to determine the difference between breast massage using the "Z" and "knuckle" techniques on breast milk production in postpartum mothers. Method: This type of research uses a Quasi experimental method, the design used is Nonequivalent control group design. This research consisted of 2 treatment groups, namely breast massage with the "Z" technique and the "Knuckles" technique. The research subjects were 20 postpartum mothers who breastfed their babies. The sampling technique uses purposive sampling. Results: The results of the research showed that out of 10 postpartum mothers after breast massage using the "Z" technique, the majority experienced smooth breast milk production, 8 of them experienced smooth breast milk production. Meanwhile, of the 10 postpartum mothers after breast massage using the "Knuckles" technique, the majority of them experienced smooth milk production, 7 of them experienced smooth milk production. It can be concluded that based on the results of the hypothesis test, the sig value (-2 tailed) = 0.429>0.05 so that there is no significant difference between breast massage using the "Z" technique and the "Knuckles" technique on the smooth flow of breast milk in postpartum mothers. Recommendation: This research recommendation can be used as a solution for postpartum mothers in overcoming the problem of smooth breastfeeding during the breastfeeding period for babies aged 0-6 months.